Purification and in vivo stability and half-life of recombinant lipid modified staphylokinase. (March 2020) - Mannully, Sheethal Thomas; Rekha, V.P.B.; Singh, N.; Shanthi, C.; Pulicherla, K.K.
Abstract: Staphylokinase (SAK), the thrombolytic protein holds a significant position in treating cardiovascular diseases. However, the rapid clearance of this protein from blood circulation reduces its effective usage and as a strategy to increase the half-life of SAK, initial work focussed on lipid modification of SAK (LMSAK) in E. coli GJ1158. Effective purification of the modified protein achieved using the two step method of hydrophobic interaction chromatography in succession with size exclusion chromatography, indicated a better yield. The thrombolytic activity of purified LMSAK analysed in heated plasma agar plate assay confirmed an enhanced activity. In vivo pharmacokinetic studies carried out for determining the half-life of LMSAK in blood circulation of mice presented that it has a half-life of 43.3 ± 3.4 min which is much higher than 21.6 ± 2.1 min that of the unmodified version of SAK. The studies confirmed the role of lipid modification as a crucial factor in confirming in vivo stability of LMSAK and proves to be beneficial in therapeutic usage. Graphical abstract: Image 1